The Importance of Polymers in Medicine and their FTIR and Raman Spectroscopic Investigations - Çelik, Sefa; AKYÜZ, SEVİM; Özel, Ayşen E. (IGI Global, 2023)
Polymers are macromolecules with a very high molecular weight that are formed as a result of one or more small molecules bonding to each other, typically by covalent bonds. The concept of macromolecules consisting of many repeating units are published in the article titled "Uber Polymerization," which was first published in 1920 by Hermann Staudinger. The idea of polymers, which have been in our lives for a long time, has thus become an important field of study. Polymers are commonly used in tissue engineering because of their properties such as biocompatibility and biodegradability. In addition, polymers have a wide range of applications in tissue regeneration, drug delivery, and wound healing. Polymers have varying structural properties based on their backbone structure, molecular weight, and crystallinity. For this cause, a great deal of study in the medicine has been based on this category of materials. This workfocuses on the importance of polymers in the medicine, 3D printed polymer composites and Fourier transform infrared, and Raman spectroscopic investigations of polymeric structures.
Source Title: Development, Properties, and Industrial Applications of 3D Printed Polymer Composites.